Macro-micro-nano integrated structured titanium silicalite molecular sieve catalyst as well as preparation method and application thereof

CN119303624APending Publication Date: 2025-01-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411272447.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

然而,该方法效率较低,反应釜的有效利用率不足20%,即每次100毫升反应釜只能制备出10毫升的结构化ZSM-5催化剂,并且所制备的ZSM-5晶体仅含有微孔结构,晶内传质受限

Benefits of technology

[0027] 1. Structural innovation: The present invention proposes a catalyst with a "macro-micro-nano" integrated structure, which combines a 3D connected hole SiC carrier, in-situ grown SiC whiskers and nickel-doped open mesoporous TS-1 Titanium silicon molecular sieve coating. This multi-scale structure effectively integrates macro channels, micro pores and nano mesopores, significantly improving the utilization efficiency, reaction rate and selectivity of the catalyst. This structural design is innovative in the field of catalysts and helps optimize the overall efficiency of the reaction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303624A_ABST
    Figure CN119303624A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic materials, and particularly relates to a macro-micro-nano integrated structured titanium silicalite molecular sieve catalyst as well as a preparation method and application thereof. According to the catalyst, SiC whiskers are grown on the surface of a 3D communicating hole SiC carrier in situ, TS-1 titanium silicalite molecular sieve precursor coating is combined with a steam crystal transformation process, and a TS-1 titanium silicalite molecular sieve coating with framework nickel doping and open mesopores is grown on the surface of the SiC whiskers, so that the loading capacity and catalytic activity of the titanium silicalite molecular sieve are effectively improved; meanwhile, excellent interface bonding force and a continuous heat conduction channel are provided through the SiC whiskers, and the heat transfer performance is enhanced. Compared with a traditional coating, the coating of the catalyst is rougher, and fluid turbulence and mass transfer efficiency are enhanced. According to the structured titanium silicalite molecular sieve catalyst, the utilization efficiency, the reaction rate and the selectivity of the catalyst are remarkably improved through coupling of macroscopic channels, micron pore channels and nano mesopores, and the structured titanium silicalite molecular sieve catalyst is particularly suitable for phenol hydroxylation reaction and olefin oxidation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of structured catalysts and their application, and specifically relates to a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst and a preparation method and application thereof. Background Art

[0002] TS-1 titanium silicalite is a microporous molecular sieve with MFI structure. Its unique catalytic performance is endowed by the titanium element embedded in the silicon-oxygen framework in a four-coordinated manner. In green catalytic oxidation reactions, TS-1 titanium silicalite exhibits high selectivity and high activity, and is particularly suitable for reactions such as phenol hydroxylation, cyclohexanone ammoximation, and olefin epoxidation.

[0003] Although TS-1 titanium silicalite has high conversion and selectivity in a variety of reactions, its powdered form faces challenges in practical applications. Although the powdered TS-1 titanium silicalite has high catalytic activity, it is easy to form a slurry during the reaction, resulting in liquid entrainment and catalyst loss, and is difficult to separate and recover. Although the combination of powdered TS-1 titanium silicalite and a binder to form a granular catalyst can achieve continuous operation in a fixed bed reactor, the inorganic binder used in the molding process will cover the active sites, increase mass transfer resistance, and reduce the utilization of the active sites of the catalyst. In addition, the fixed bed has poor heat transfer performance, which can easily lead to catalyst coking and deactivation, thereby affecting reaction efficiency and product selectivity. Therefore, it is urgent to develop new catalysts and processes to improve the utilization rate and anti-coking ability of TS-1 titanium silicalite.

[0004] TS-1 titanium silicalite is loaded on a regular structured carrier in the form of a coating to make a structured catalyst. Compared with a fixed bed of particle stacking, it has a higher area / volume ratio and a lower pressure drop, can provide more active sites and reduce energy consumption. The diffusion path of the coated catalyst is shorter, which helps to improve product selectivity and slow down the coking and deactivation of the catalyst. The high thermal conductivity carrier material can effectively disperse the reaction heat and suppress the deactivation problem caused by excessive local temperature. In addition, the modular design of the structured catalyst simplifies the assembly and maintenance of the reactor. By optimizing the geometric configuration of the coating and the carrier, the concentration distribution of the reactants is improved, and the reaction efficiency and product selectivity are improved.

[0005] At present, the method for preparing TS-1 titanium silicon molecular sieve coating mainly includes coating method and in-situ hydrothermal synthesis method, but from the perspective of the macroscopic structure of the coating, no matter which method is used, increasing the molecular sieve loading usually requires increasing the coating thickness. However, as the coating thickness increases, its permeability will decrease significantly. Thicker coatings will increase the diffusion resistance of reactants and products in the coating, resulting in reduced mass transfer and heat transfer efficiency. This phenomenon limits the overall performance of the catalyst, especially in liquid phase reactions, where thicker coatings may lead to low reaction efficiency and increase the risk of catalyst deactivation. Therefore, while pursuing high loading, it is necessary to comprehensively consider the balance between coating thickness and permeability to ensure the effective utilization and stability of the catalyst. Although traditional methods improve partial permeability by optimizing the intercrystalline and intracrystalline porosity of the coating, the effect is limited in the case of thick coatings (Patent Publication No. CN113751067A). Therefore, in order to further improve the activity and stability of the molecular sieve coating, it is necessary to increase the roughness of the coating surface to strengthen the mass transfer and heat transfer performance inside the coating, thereby improving the penetration depth and catalytic efficiency of the fluid.

[0006] In the 2015 Journal of Catalysis, Jiao Yilai used carbon thermal reduction technology to in-situ grow one-dimensional SiC whiskers on the surface of a foam SiC carrier, significantly increasing the specific surface area of ​​the carrier. Subsequently, ZSM-5 molecular sieves were in-situ grown on the surface of SiC whiskers by hydrothermal synthesis technology, increasing the molecular sieve loading from less than 8% to 28%. However, this method is inefficient, and the effective utilization rate of the reactor is less than 20%, that is, each 100 ml reactor can only produce 10 ml of structured ZSM-5 catalyst, and the prepared ZSM-5 crystals only contain microporous structures, and intracrystalline mass transfer is limited. In addition, in the 2022 Chemical Engineering Research and Design journal, Jiao Yilai prepared a cobalt manganese oxide / SiC whisker / foam SiC structured catalyst based on SiC whisker modified foam SiC carrier. Compared with the unmodified foam SiC carrier, the cobalt manganese oxide loading increased by 2 times, effectively preventing the cracking and shedding of tungsten oxide. In the catalytic oxidation of toluene, the structured catalyst exhibited remarkably high activity and high thermal stability.

[0007] In general, TS-1 titanium silicalite exhibits excellent performance in catalytic reactions due to its high selectivity and high activity, but its microporous structure limits the mass transfer efficiency and affects the utilization of active sites. Loading TS-1 titanium silicalite on a regular carrier in the form of a coating can alleviate these problems, but increasing the coating thickness often leads to a decrease in permeability. In order to improve the activity and stability of the catalyst, it is particularly important to increase the roughness of the coating surface. Combining carbon thermal reduction and hydrothermal synthesis technology can significantly improve the loading capacity and mass transfer performance of the coating, but the preparation process still needs to be further optimized to meet the needs of industrial applications. Summary of the invention

[0008] The purpose of the present invention is to provide a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst and its preparation method and application. The structured titanium silicon molecular sieve catalyst obtains a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst with high heat transfer capacity, high permeability and high mass transfer capacity through the coupling of macro channels, micron pores and nano-mesopores, which significantly improves the utilization efficiency, reaction rate and selectivity of the catalyst, and is particularly suitable for phenol hydroxylation reaction and olefin oxidation reaction.

[0009] The technical solution of the present invention is:

[0010] A "macro-micro-nano" integrated structured titanium silicalite catalyst, which consists of a 3D interconnected pore SiC carrier, SiC whiskers grown in situ on the surface of the 3D interconnected pore SiC carrier, and a skeleton nickel-doped, open mesoporous TS-1 titanium silicalite coating supported on the surface of the SiC whiskers.

[0011] The "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst has a 3D interconnected pore SiC carrier with a three-dimensional interconnected network structure, which is composed of Si and SiC phases, and the mass percentage of silicon is 5-20%; SiC whiskers are epitaxially grown on the 3D interconnected pore SiC carrier as a substrate, and a 0.1-5 nanometer amorphous silicon dioxide layer is coated on the surface of the SiC whiskers; the skeleton nickel-doped TS-1 titanium silicon molecular sieve grown on the surface of the SiC whiskers has a skeleton nickel content of 0.1-3wt%, a skeleton titanium content of 0.1-2.5wt%, and the skeleton nickel-doped TS-1 titanium silicon molecular sieve crystal has an open mesoporous structure with a mesopore volume of 0.3-1.2cm 3 / g, with an external surface area of ​​200 to 400 m 2 / g.

[0012] The "macro-micro-nano" integrated structured titanium silicalite catalyst is a TS-1 titanium silicalite doped with skeleton nickel. Nickel exists in the tetracoordinate skeleton of the TS-1 titanium silicalite in the form of nickel ions, which effectively reduces the charge density around the titanium ions and improves their catalytic activity.

[0013] The preparation method of the "macro-micro-nano" integrated structured titanium silicalite catalyst is characterized in that SiC whiskers are grown in situ on the surface of a 3D connected-pore SiC carrier, and a TS-1 titanium silicalite coating with skeleton nickel doping and open mesopores is grown on the surface of the SiC whiskers through TS-1 titanium silicalite precursor coating combined with a steam crystallization process, thereby effectively improving the loading capacity and catalytic activity of the titanium silicalite. At the same time, the SiC whiskers provide excellent interface bonding strength and continuous heat conduction channels to enhance heat transfer performance.

[0014] The preparation method of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst and the preparation method of the TS-1 titanium silicon molecular sieve coating on the surface of SiC whiskers include: firstly coating the surface of SiC whiskers with an aged TS-1 titanium silicon molecular sieve precursor; and then treating the surface of SiC whiskers with high temperature and high pressure water vapor or organic amine vapor to form a skeleton nickel-doped open mesoporous TS-1 titanium silicon molecular sieve coating.

[0015] The preparation method of the "macro-micro-nano" integrated structured titanium silicalite molecular sieve catalyst is that the aged TS-1 titanium silicalite molecular sieve precursor contains the original zeolite unit, and the nickel ions are protected by a complexing agent to prevent the nickel ions from precipitating in the form of metallic nickel or nickel oxide particles during the precursor aging process and in the vapor phase.

[0016] The preparation method of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst, the preparation method of the aging treated TS-1 titanium silicon molecular sieve precursor comprises: first, after deionized water and tetrapropylammonium hydroxide are mixed evenly, a silicon source is added dropwise until the mixed solution is clarified and evenly distributed; then, a titanium source and a nickel source protected by a complexing agent are added, and aging is performed by condensing and refluxing at 50 to 90° C. for 3 to 24 hours;

[0017] Among them, the molar ratio of silicon source, titanium source, nickel source, complexing agent, tetrapropylammonium hydroxide and deionized water is 1:0.01~0.1:0.01~0.1:0.005~0.5:0.1~0.5:10~50; the nickel source used is one or more of nickel sulfate, nickel phosphate, nickel nitrate, nickel acetate, nickel chloride and nickel carbonate; the complexing agent used is one or more of ethylenediamine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenediamine and polyethylenepolyamine.

[0018] The preparation method of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst comprises the following steps: after coating the aged TS-1 titanium silicon molecular sieve precursor onto the surface of SiC whiskers, treating the catalyst in water vapor at 130 to 200°C or in water vapor with organic amine added for 12 to 96 hours; the coating is performed 1 to 3 times, and after coating, the excess TS-1 titanium silicon molecular sieve precursor is removed, and the catalyst is treated at room temperature to 100°C for 1 to 12 hours; wherein the organic amines that can be used include one or more of ammonia water, methylamine, ethylamine, ethylenediamine, tetramethylammonium hydroxide, tetramethylammonium bromide, tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium bromide and tetrapropylammonium hydroxide; and the molar percentage of the organic amine in the water vapor with the organic amine added is 0.01 to 2%.

[0019] The preparation method of the "macro-micro-nano" integrated structured titanium silicalite molecular sieve catalyst is characterized in that the aging step of the TS-1 titanium silicalite precursor can enable the precursor to have some zeolite structural characteristics, namely, the original zeolite structure, which promotes the rapid nucleation and crystallization of the molecular sieve during steam treatment; during the steam treatment process, nickel is incorporated into the four-coordinate framework of the TS-1 titanium silicalite molecular sieve and exists in the form of nickel cations; at the same time, the aged molecular sieve precursor is assembled under the induction of the original zeolite to form a TS-1 titanium silicalite molecular sieve single crystal with an open mesoporous structure.

[0020] The application of the "macro-micro-nano" integrated structured titanium silicalite catalyst, which obtains a "macro-micro-nano" integrated structured titanium silicalite catalyst with high heat transfer capacity, high permeability and high mass transfer capacity through the coupling of macro channels, micron pores and nano-mesopores. The catalyst is used in a fixed bed reactor to achieve a highly coupled design of fluid flow, heat transfer, mass transfer and catalytic reaction, which significantly improves the reaction efficiency and stability of the catalyst; the catalyst exhibits high phenol conversion rate, high hydroquinone selectivity and excellent anti-coking ability in the fixed bed phenol hydroxylation reaction to produce hydroquinone; and exhibits high propylene conversion rate, high propylene oxide selectivity and anti-carbon deposition ability in the fixed bed propylene epoxidation reaction to produce propylene oxide.

[0021] The design idea of ​​the present invention is:

[0022] The present invention uses one-dimensional SiC whiskers on the surface of a SiC carrier with regular 3D interconnected pores as a medium to establish a bridge between an open mesoporous TS-1 titanium silicon molecular sieve and a 3D interconnected pore SiC carrier, thereby realizing the construction of a structured TS-1 titanium silicon molecular sieve catalyst that integrates macroscopic (millimeter to centimeter channels of a structured catalyst carrier), microscopic (micrometer channels between SiC whiskers) and nanoscopic (nanoscale mesopores inside TS-1 titanium silicon molecular sieve crystals). The present invention prepares a skeleton nickel-doped open mesoporous TS-1 titanium silicon molecular sieve coating by coating an aged TS-1 titanium silicon molecular sieve precursor on the surface of the SiC whisker and combining it with a steam crystallization process. In order to prevent nickel from forming metallic nickel or nickel oxide particles during the aging and steam phase conversion process of the molecular sieve precursor, the present invention uses a coordination complexation method to protect nickel ions. The new catalyst combines large porosity, "micro-nano" coupling, porous structure, large specific surface area, excellent thermal conductivity and permeability, and unique shape factor, which are conducive to improving the flow field, temperature field distribution, mass transfer, heat transfer and reaction. The factors efficiently couple to achieve the matching coupling of "flow-transfer-reaction", thereby improving the catalyst utilization efficiency in the fixed-bed phenol hydroxylation reaction process, enhancing the steady-state reaction rate and selectivity, and slowing down the deactivation of the catalyst.

[0023] In the skeleton nickel-doped TS-1 titanium silicalite of the present invention, nickel exists in the tetracoordinate framework of the TS-1 titanium silicalite in the form of nickel ions, which effectively reduces the charge density around the titanium ions, thereby improving its catalytic activity. The open mesoporous structure of the TS-1 titanium silicalite crystal can effectively improve the utilization rate of the active sites in the molecular sieve crystal, and effectively inhibit the formation of coking and carbon deposition. The SiC whisker coating structure wrapped with the TS-1 titanium silicalite significantly improves the fluid turbulence intensity and penetration depth inside the coating, thereby improving the mass transfer and heat transfer rate of the catalyst. The SiC whiskers have good interface bonding with the 3D interconnected pore SiC carrier, and provide a continuous heat conduction channel, which strengthens the heat transfer between the coating and the carrier. The 3D interconnected pore SiC carrier optimizes the flow field distribution and further enhances the mass transfer and heat transfer performance.

[0024] In the present invention, the aging step of the TS-1 titanium silicon molecular sieve precursor enables the precursor to have some zeolite structural characteristics, which promotes the rapid nucleation and crystallization of the molecular sieve during the steam treatment process. During the steam treatment process, nickel is incorporated into the four-coordinate framework of the TS-1 titanium silicon molecular sieve and exists in the form of nickel cations. At the same time, the aged molecular sieve precursor is assembled under the induction of the original zeolite to form a TS-1 titanium silicon molecular sieve single crystal with an open mesoporous structure.

[0025] In the present invention, when the catalyst is used in a fixed bed reactor, a highly coupled design of fluid flow, heat transfer, mass transfer and catalytic reaction can be realized, and the reaction efficiency and stability of the catalyst can be significantly improved. The catalyst exhibits high phenol conversion rate, high hydroquinone selectivity and excellent anti-coking ability in the fixed bed phenol hydroxylation reaction to produce hydroquinone; and exhibits high propylene conversion rate, high propylene oxide selectivity and anti-coking ability in the fixed bed propylene epoxidation reaction to produce propylene oxide.

[0026] The present invention has the following advantages and beneficial effects:

[0027] 1. Structural innovation: This invention proposes a catalyst with an integrated "macro-micro-nano" structure, which combines a 3D interconnected pore SiC carrier, in-situ grown SiC whiskers, and a nickel-doped open mesoporous TS-1 titanium silicon molecular sieve coating. This multi-scale structure effectively integrates macro channels, micron channels, and nano-mesopores, significantly improving the utilization efficiency, reaction rate, and selectivity of the catalyst. This structural design is innovative in the field of catalysts and helps optimize the overall efficiency of the reaction process.

[0028] 2. Material innovation: The present invention uses nickel-doped TS-1 titanium silicon molecular sieve and combines it with SiC whiskers. Nickel doping can effectively reduce the charge density around titanium ions, thereby improving catalytic activity; SiC whiskers provide excellent interface bonding and heat conduction channels, significantly enhancing the heat transfer performance of the catalyst. This material combination demonstrates unique innovation and significantly improves the performance and application range of the catalyst.

[0029] 3. Preparation process innovation: The present invention adopts a method of growing a titanium silicon molecular sieve coating on the surface of SiC whiskers using a steam crystallization process. This process not only improves the adhesion and stability of the coating, but also increases the fluid turbulence and mass transfer efficiency by increasing the roughness of the coating. In addition, the nickel ion protection strategy in the aging treatment can prevent the precipitation of nickel ions during the preparation process, ensuring the high activity of the catalyst. These process innovations effectively improve the overall performance of the catalyst.

[0030] 4. Application innovation: The catalyst of the present invention exhibits excellent catalytic performance in phenol hydroxylation and propylene epoxidation reactions, specifically high reaction conversion rate, high selectivity and strong resistance to carbon deposition. These application scenarios not only demonstrate the versatility of the catalyst, but also prove its potential advantages in industrial reactions.

[0031] In summary, the present invention has shown significant innovation in structural design, material selection, preparation process and application, and has important technical advantages and broad application prospects. Compared with traditional coatings, the coating of the catalyst is rougher, which further enhances fluid turbulence and mass transfer efficiency. In addition, SiC whisker modification significantly increases the surface area of ​​the carrier, a single coating can achieve higher loads, and shorten the preparation cycle; the effective utilization rate of the reactor in the steam phase conversion process is greater than 80%, reducing the discharge of three wastes. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of a foam SiC carrier with SiC whiskers grown on its surface.

[0033] Figure 2 This is a scanning electron microscope image of SiC whiskers on the surface of the foam SiC carrier (partial magnification).

[0034] Figure 3 This is a scanning electron microscope image of SiC whiskers grown on TS-1 titanium silicon molecular sieve.

[0035] Figure 4 This is a scanning helium ion beam electron microscope image of TS-1 titanium silicon molecular sieve with open mesopores on the surface of SiC whiskers.

[0036] Figure 5 High-resolution transmission electron microscopy image of TS-1 titanium silicate molecular sieve with open mesopores on the surface of SiC whiskers.

[0037] Figure 6 This is the catalyst physical adsorption pore size distribution curve of the "macro-micro-nano" integrated structured titanium silicon molecules.

[0038] Figure 7 Mercury entry and exit curves of the catalyst of the "macro-micro-nano" integrated structured titanium-silicon molecule. DETAILED DESCRIPTION

[0039] In the specific implementation process, the catalyst of the present invention uses 3D interconnected pore SiC with in-situ growth of SiC whiskers on the surface as a carrier, and grows a TS-1 titanium silicon molecular sieve coating with skeleton nickel doping and open mesopores on the surface of the SiC whiskers through TS-1 titanium silicon molecular sieve precursor coating combined with steam crystallization process. This construction strategy effectively improves the loading capacity and catalytic activity of titanium silicon molecular sieve, while providing excellent interface bonding and continuous heat conduction channels through SiC whiskers, thereby enhancing heat transfer performance.

[0040] Below, the present invention is further described in detail by examples.

[0041] Example 1

[0042] In this embodiment, a method for preparing a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst comprises the following steps:

[0043] First, a TS-1 titanium silicalite precursor containing an original zeolite unit is prepared. After deionized water and tetrapropylammonium hydroxide are uniformly mixed, ethyl orthosilicate is slowly added dropwise until the mixed solution is completely clear and uniform.

[0044] Then, tetrabutyl titanate and nickel nitrate protected by diethylenetriamine as a complexing agent were added, and condensation reflux was performed at 80° C. for 12 hours to complete the aging process.

[0045] Wherein, the molar ratio of tetraethyl orthosilicate, tetrabutyl titanate, nickel nitrate, diethylenetriamine, tetrapropylammonium hydroxide and deionized water is 1:0.02:0.01:0.015:0.3:20.

[0046] Next, the aged TS-1 titanium silicon molecular sieve precursor was evenly coated on the surface of the SiC whisker. After one coating, the excess precursor was removed and the SiC whisker was left to stand at room temperature for 12 hours. The SiC carrier used was a 3D interconnected pore SiC carrier containing 10% silicon by mass, with a pore size of 20ppi; the SiC whiskers grew perpendicular to the foam SiC carrier, with a whisker diameter of 1 micron and a length of 20 microns. The scanning electron microscope image of the surface-grown SiC whisker foam SiC carrier is shown in Figure 1 , Figure 2 .

[0047] Finally, the support coated with the molecular sieve precursor was placed in a stainless steel reactor containing polytetrafluoroethylene and treated in water vapor at 190° C. for 48 hours. The volume of the catalyst was 900 ml, the effective volume of the reactor was 1000 ml, and the volume of water was 50 ml.

[0048] After the reaction was completed, the sample was washed several times in deionized water at 100°C and then dried at 100°C for 12 hours. The dried sample was calcined in a muffle furnace at 550°C for 6 hours to obtain a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst. Figure 3 As shown in the figure, the SEM image of SiC whiskers growing on TS-1 titanium silicon molecular sieve shows that TS-1 titanium silicon molecular sieve crystals wrap around the SiC whiskers and do not block the pores between the SiC whiskers. Figure 4 As shown in Figure 1, the scanning helium ion beam electron microscope image of the open mesoporous TS-1 titanium silicon molecular sieve on the surface of SiC whiskers; Figure 5 As shown, the high-resolution transmission electron microscopy image of the open mesoporous TS-1 titanium silicate molecular sieve on the surface of SiC whiskers; Figure 4-Figure 5It can be seen that TS-1 titanium silicalite has open mesopores from the inside to the outside. In the "macro-micro-nano" integrated structured titanium silicalite catalyst, the loading amount of TS-1 titanium silicalite is 40wt%, the crystal size is 500 nanometers, the silicon-titanium atomic ratio is 50, and it contains 1.5wt% of tetracoordinated skeleton nickel. The specific surface area (BET) of the "macro-micro-nano" integrated structured titanium silicalite catalyst is 200m 2 / g, micropore surface area is 120m 2 / g, the surface area of ​​the composite material measured by t-plot method is 100m 2 / g, micropore volume is 0.07cm 3 / g. The mercury injection method was used to measure the amount of mercury injected into the pores with a diameter of 50nm to 60μm, which was 0.6mL / g ( Figure 6 ). Using the Barrett-Joyner-Halenda (BJH) method, the pore volume in the pore size range of 2 to 50 nm is 0.45 cm 3 / g, and the mesopores are concentrated around 10 nanometers ( Figure 7 ).

[0049] In the fixed-bed phenol hydroxylation to produce hydroquinone, the "macro-micro-nano" integrated structured titanium silicon molecular sieve was used as a catalyst, water was used as a solvent, the molar ratio of phenol to hydrogen peroxide was 3:1, the mass ratio of phenol to titanium silicon molecular sieve was 20:1, and the reaction temperature was 80°C. The reaction was carried out continuously for 1,000 hours, during which the conversion rate of phenol remained above 90%, the selectivity of catechol was 10%, the selectivity of hydroquinone was 90%, and no by-products were generated.

[0050] The epoxidation of propylene was carried out in a fixed bed reactor, using the "macro-micro-nano" integrated structured titanium silicalite as a catalyst, methanol as a solvent, and a catalyst loading of 50 ml. The reaction conditions were as follows: temperature of 40°C, pressure of 3.0 MPa, mass space velocity of propylene relative to TS-1 titanium silicalite of 30 h-1, and a molar ratio of propylene to H2O2 of 3.0. In the long-term continuous reaction of 2000 hours, the conversion rate of H2O2 remained above 99%, and the selectivity of propylene oxide was greater than 99%.

[0051] Example 2

[0052] In this embodiment, a method for preparing a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst comprises the following steps:

[0053] First, a TS-1 titanium silicalite precursor containing an original zeolite unit is prepared. After deionized water and tetrapropylammonium hydroxide are uniformly mixed, ethyl orthosilicate is added dropwise until the solution is clear and uniform.

[0054] Then, tetraethyl titanate and nickel sulfate protected by ethylenediamine as a complex were added, and condensation reflux was performed at 90° C. for 18 hours to complete the aging process.

[0055] Wherein, the molar ratio of tetraethyl orthosilicate, tetraethyl titanate, nickel sulfate, ethylenediamine, tetrapropylammonium hydroxide and deionized water is 1:0.01:0.015:0.02:0.2:30.

[0056] Next, the aged TS-1 titanium silicon molecular sieve precursor was evenly coated on the surface of the SiC whisker. After one coating, the excess precursor was removed and the SiC whisker was placed at 60°C for 4 hours. The SiC carrier used was a 3D interconnected pore SiC carrier containing 15% mass fraction of silicon and a pore size of 30ppi; the SiC whiskers grew vertically on the foam SiC carrier, with a whisker diameter of 500 nanometers and a length of 25 microns.

[0057] Finally, the support coated with the molecular sieve precursor was placed in a stainless steel reactor containing polytetrafluoroethylene and treated in water vapor at 180° C. for 72 hours. The volume of the catalyst was 900 ml, the effective volume of the reactor was 1000 ml, and the volume of water was 30 ml.

[0058] After the reaction is completed, the sample is washed several times in deionized water at 100°C and then dried at 100°C for 12 hours. The dried sample is calcined at 550°C in a muffle furnace for 6 hours. The final "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst has a loading of 45wt% of TS-1 titanium silicon molecular sieve, a crystal size of 800 nanometers, a silicon-titanium atomic ratio of 80, and contains 2.2wt% of tetracoordinated skeleton nickel. The specific surface area (BET) of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst is 230m 2 / g, micropore surface area is 130m 2 / g, the surface area of ​​the composite material measured by t-plot method is 120m 2 / g, micropore volume is 0.10cm 3 / g. The pore volume of the pores with a pore size range of 2 to 50 nm is estimated by the Barrett-Joyner-Halenda (BJH) method to be 0.30 cm 3 / g; measured by mercury intrusion method, the pore volume in the range of 50 to 500 μm is 1.50 cm 3 / g.

[0059] In the fixed-bed phenol hydroxylation to produce hydroquinone, the "macro-micro-nano" integrated structured titanium silicon molecular sieve was used as a catalyst, water was used as a solvent, the molar ratio of phenol to hydrogen peroxide was 3:1, the mass ratio of phenol to titanium silicon molecular sieve was 20:1, and the reaction temperature was 80°C. The reaction was carried out continuously for 1,000 hours, during which the conversion rate of phenol remained above 92%, the selectivity of catechol was 8%, the selectivity of hydroquinone was 92%, and no by-products were generated.

[0060] The epoxidation of propylene was carried out in a fixed bed reactor, using the "macro-micro-nano" integrated structured titanium silicalite as a catalyst, methanol as a solvent, and a catalyst loading of 50 ml. The reaction conditions were as follows: temperature of 40°C, pressure of 3.0 MPa, mass space velocity of propylene relative to TS-1 titanium silicalite of 20 h-1, and a molar ratio of propylene to H2O2 of 3.0. In the long-term continuous reaction of 2000 hours, the conversion rate of H2O2 remained above 99.5%, and the selectivity of propylene oxide was greater than 99.5%.

[0061] Example 3

[0062] In this embodiment, a method for preparing a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst comprises the following steps:

[0063] First, a TS-1 titanium silicalite precursor containing an original zeolite unit is prepared. After deionized water and tetrapropylammonium hydroxide are uniformly mixed, ethyl orthosilicate is added dropwise until the mixed solution is completely clarified.

[0064] Subsequently, titanium tetrachloride and nickel acetate protected by ethylenediamine as a complexing agent were added, and condensation reflux was performed at 90° C. for 18 hours to complete the aging process.

[0065] Wherein, the molar ratio of tetraethyl orthosilicate, titanium tetrachloride, nickel acetate, ethylenediamine, tetrapropylammonium hydroxide and deionized water is 1:0.02:0.02:0.05:0.25:25.

[0066] Next, the aged TS-1 titanium silicon molecular sieve precursor was evenly coated on the surface of the SiC whisker. After one coating, the excess precursor was removed and the SiC whisker was left to stand at 40°C for 12 hours. The SiC carrier used was a 3D interconnected pore SiC carrier containing 20% ​​mass fraction of silicon and a pore size of 50ppi; the SiC whiskers grew perpendicular to the foam SiC carrier, with a whisker diameter of 2 microns and a length of 50 microns.

[0067] Finally, the support coated with the molecular sieve precursor was placed in a stainless steel reactor containing polytetrafluoroethylene and treated in water vapor at 180° C. for 72 hours. The volume of the catalyst was 900 ml, the effective volume of the reactor was 1000 ml, and the volume of water was 30 ml.

[0068] After the reaction is completed, the sample is repeatedly washed in deionized water at 100°C and then dried at 100°C for 12 hours. The dried sample is calcined at 550°C in a muffle furnace for 6 hours. The final "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst has a loading of 50wt% of TS-1 titanium silicon molecular sieve, a crystal size of 600 nanometers, a silicon-titanium atomic ratio of 50, and contains 1.8wt% of tetracoordinated skeleton nickel. The specific surface area (BET) of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst is 250m 2 / g, micropore surface area is 150m 2 / g, the surface area of ​​the composite material measured by t-plot method is 140m 2 / g, micropore volume is 0.11cm 3 / g. The pore volume of the pores with a pore size range of 2 to 50 nm is estimated by the Barrett-Joyner-Halenda (BJH) method to be 0.40 cm 3 / g; measured by mercury intrusion method, the pore volume in the range of 50 to 500 μm is 2.0 cm 3 / g.

[0069] In the fixed-bed phenol hydroxylation to produce hydroquinone, the "macro-micro-nano" integrated structured titanium silicon molecular sieve was used as a catalyst, water was used as a solvent, the molar ratio of phenol to hydrogen peroxide was 3:1, the mass ratio of phenol to titanium silicon molecular sieve was 20:1, and the reaction temperature was 80°C. The reaction was carried out continuously for 1,000 hours, during which the conversion rate of phenol remained above 95%, the selectivity of catechol was 87%, the selectivity of hydroquinone was 93%, and no by-products were generated.

[0070] The epoxidation of propylene was carried out in a fixed bed reactor, using the "macro-micro-nano" integrated structured titanium silicalite as a catalyst, methanol as a solvent, and a catalyst loading of 50 ml. The reaction conditions were as follows: temperature of 40°C, pressure of 3.0 MPa, mass space velocity of propylene relative to TS-1 titanium silicalite of 50 h-1, and a molar ratio of propylene to H2O2 of 3.0. In the long-term continuous reaction of 2000 hours, the conversion rate of H2O2 remained above 95%, and the selectivity of propylene oxide was greater than 99%.

[0071] The implementation results show that the present invention provides a method for preparing a "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst, by coating the prepared TS-1 titanium silicon molecular sieve precursor on the surface of SiC whiskers and performing hydrothermal treatment at high temperature and high pressure, and finally obtaining a highly efficient catalyst. Each embodiment shows that the catalyst prepared under different conditions exhibits high conversion rate and high selectivity in the phenol hydroxylation reaction, and no by-products are generated, indicating that the catalyst has excellent structural stability and catalytic performance, and is suitable for industrial catalytic applications.

Claims

1. A "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst, characterized in that: The catalyst consists of a 3D interconnected pore SiC carrier, SiC whiskers grown in situ on the surface of the 3D interconnected pore SiC carrier, and a skeleton nickel-doped, open mesoporous TS-1 titanium silicon molecular sieve coating loaded on the surface of the SiC whiskers.

2. The "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 1, characterized in that: The 3D interconnected pore SiC carrier has a three-dimensional interconnected network structure, which is composed of two phases of Si and SiC, and the mass percentage of silicon is 5-20%. The SiC whisker is epitaxially grown on the 3D interconnected pore SiC carrier as a substrate, and a 0.1-5 nanometer amorphous silicon dioxide layer is coated on the surface of the SiC whisker. The skeleton nickel-doped TS-1 titanium silicon molecular sieve grown on the surface of the SiC whisker has a skeleton nickel content of 0.1-3wt%, a skeleton titanium content of 0.1-2.5wt%, and the skeleton nickel-doped TS-1 titanium silicon molecular sieve crystal has an open mesoporous structure with a mesopore volume of 0.3-1.2cm 3 / g, with an external surface area of ​​200-400m 2 / g.

3. The "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 2, characterized in that: In the framework nickel-doped TS-1 titanium silicalite, nickel exists in the tetracoordinate framework of the TS-1 titanium silicalite in the form of nickel ions, which effectively reduces the charge density around the titanium ions and improves their catalytic activity.

4. A method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to any one of claims 1 to 3, characterized in that: The catalyst uses in-situ growth of SiC whiskers on the surface of a 3D interconnected-pore SiC carrier. Through TS-1 titanium silicalite precursor coating combined with steam crystallization technology, a TS-1 titanium silicalite coating with skeleton nickel doping and open mesopores is grown on the surface of the SiC whiskers, effectively increasing the loading capacity and catalytic activity of the titanium silicalite. At the same time, the SiC whiskers provide excellent interface bonding strength and continuous heat conduction channels, enhancing heat transfer performance.

5. The method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 4, characterized in that: The preparation method of the TS-1 titanium silicon molecular sieve coating on the surface of SiC whiskers comprises: firstly coating the surface of the SiC whiskers with an aged TS-1 titanium silicon molecular sieve precursor; and then treating the surface of the SiC whiskers with high temperature and high pressure water vapor or organic amine vapor to form a skeleton nickel-doped open mesoporous TS-1 titanium silicon molecular sieve coating on the surface of the SiC whiskers.

6. The method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 5, characterized in that: The aged TS-1 titanium silicalite precursor contains the original zeolite unit, and the nickel ions are protected by a complexing agent to prevent the nickel ions from precipitating in the form of metallic nickel or nickel oxide particles during the precursor aging process and in the vapor phase.

7. The method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 5 or 6, characterized in that: The preparation method of the TS-1 titanium silicon molecular sieve precursor subjected to aging treatment comprises: first, mixing deionized water and tetrapropylammonium hydroxide uniformly, and then adding a silicon source dropwise until the mixed solution is clarified and uniform; then, adding a titanium source and a nickel source protected by a complexing agent, and condensing and refluxing at 50 to 90° C. for 3 to 24 hours for aging; Among them, the molar ratio of silicon source, titanium source, nickel source, complexing agent, tetrapropylammonium hydroxide and deionized water is 1:0.01~0.1:0.01~0.1:0.005~0.5:0.1~0.5:10~50; the nickel source used is one or more of nickel sulfate, nickel phosphate, nickel nitrate, nickel acetate, nickel chloride and nickel carbonate; the complexing agent used is one or more of ethylenediamine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenediamine and polyethylenepolyamine.

8. The method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 7, characterized in that: After coating the aged TS-1 titanium silicon molecular sieve precursor onto the surface of the SiC whisker, the precursor is treated in water vapor at 130 to 200° C. or in water vapor with an organic amine added thereto for 12 to 96 hours; the coating is performed 1 to 3 times, and after coating, the excess TS-1 titanium silicon molecular sieve precursor is removed, and the precursor is treated at room temperature to 100° C. for 1 to 12 hours; the organic amines that can be used include one or more of ammonia water, methylamine, ethylamine, ethylenediamine, tetramethylammonium hydroxide, tetramethylammonium bromide, tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium bromide and tetrapropylammonium hydroxide; the molar percentage of the organic amine in the water vapor with the organic amine added thereto is 0.01 to 2%.

9. The method for preparing the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to claim 8, characterized in that: The aging step of the TS-1 titanium silicalite precursor can make the precursor have some zeolite structural characteristics, namely the original zeolite structure, which promotes the rapid nucleation and crystallization of the molecular sieve during the steam treatment process; during the steam treatment process, nickel is incorporated into the four-coordinate framework of the TS-1 titanium silicalite and exists in the form of nickel cations; at the same time, the aged molecular sieve precursor is assembled under the induction of the original zeolite to form TS-1 titanium silicalite single crystals with an open mesoporous structure.

10. An application of the "macro-micro-nano" integrated structured titanium silicon molecular sieve catalyst according to any one of claims 1 to 9, characterized in that: The structured titanium silicalite catalyst is obtained by coupling macro channels, micron pores and nano-mesopores to obtain a "macro-micro-nano" integrated structured titanium silicalite catalyst with high heat transfer capacity, high permeability and high mass transfer capacity. The catalyst is used in a fixed bed reactor to achieve a highly coupled design of fluid flow, heat transfer, mass transfer and catalytic reaction, which significantly improves the reaction efficiency and stability of the catalyst; the catalyst exhibits high phenol conversion rate, high catechol selectivity and excellent anti-coking ability in the fixed-bed phenol hydroxylation reaction to produce hydroquinone; in the fixed-bed propylene epoxidation reaction to produce propylene oxide, it exhibits high propylene conversion rate, high propylene oxide selectivity and anti-carbon deposition ability.

Citation Information

Patent Citations

  • Hierarchically porous titanium silicalite molecular sieve coating, preparation method and application thereof

    CN113751067A

Cited By

  • Whisker array SiC palladium-loaded iron catalyst as well as preparation method and application thereof

    CN121775883A